Comparing extremist perpetrators of suicide and non-suicide attacks in the United States - Freilich, Joshua D. (Terrorism and political violence, 2019)
This study explores differences in perpetrators of suicide attacks and non-suicide attacks in the United States. The study uses data on far-right and Al Qaeda and affiliated/inspired terrorists between 1990 and 2013 from the United States Extremist Crime Database. Our analysis estimates logistic regression models to test whether suicide attackers were more likely to have exhibited specific risk factors for suicidality, while examining other prominent claims regarding patterns of suicide terrorism. Suicide attackers were no more likely than non-suicide attackers to have previously attempted suicide or to have been diagnosed as mentally ill. Suicide attackers were more likely, though, to have a history of substance abuse, to be loners, have served in the military, participated in paramilitary training, and be more ideologically committed to the cause. We found that Al Qaeda affiliated/inspired attackers were more likely than far-right attackers to have engaged in a suicide mission. With the current focus on Americans traveling to Syria and Iraq to receive training and fight for jihadist movements (e.g., the Islamic State), our findings appear relevant. Observers have expressed concern that these fighters may return and then commit attacks in their homeland. Law enforcement could make use of this study’s findings.